EVALUATION OF THE 2013 CURRICULUM IMPLEMENTATION FOR PHYSICAL EDUCATION, SPORT AND HEALTH - Boleng, Lukas Maria; Rahayu, Tandiyo (The Journal of Educational Development, 2016)
This research is meant to find out the students’ reaction on the learning environment and learning achievement of Physical Education, Sport and Health (PESH) based on 2013 curriculum, to find out the students’ behaviour in PESH teaching and learning, and to find out the overall implementation of 2013 curriculum. This is an evaluation study by using a quantitative method. The sample was seventh and eighth graders, teachers, and parents. The data were collected by using questionnaires and analyzed by using a descriptive quantitative analysis. The results of the study show that the students’ learning achievement is not yet high and the students perceive that the learning environment for the 2013 curriculum implementation pada pilot JHSs in South Central Timor District is not yet adequate. On the students’ behaviour on the school learning environment, the students have not applied them in their daily life activities. Additionally, the 2013 curriculum is not yet implemented comprehensively as expected.